PANDANGAN ALKITAB MENGENAI PERNIKAHAN YANG TIDAK SEIMAN - Victoria Woen (Sekolah Tinggi Teologi Excelsius, 2020)
General theory: Marriage is an institution authorized by God which involves the union of a man and a woman as